2019
DOI: 10.1111/joor.12926
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anamnestic symptoms and clinical signs of temporomandibular disorders in adolescents—Results of the epidemiologic LIFE Child Study

Abstract: Background Prevalence values for symptoms and signs of temporomandibular disorders (TMD) in adolescents vary within the literature due to differences in set‐ups of examination protocols. Objectives The objective was to present prevalence values for symptoms and signs of TMD in German adolescents that were observed within a standardised examination. Prevalence values comparing gender or pubertal status should be investigated. Methods A cross‐sectional sample of the LIFE Child Study aged 10 to 18 was examined. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 27 publications
2
24
0
2
Order By: Relevance
“…Temporomandibular joint (TMJ) sounds are categorized as cardinal symptoms of temporomandibular disorders (TMD) [1]. According to a systematic review, 14.0% of the children or adolescents had clinical TMJ sounds [2], while a current investigation detected an even higher percentage-up to 31.9%-for German adolescents [3]. The gap between prevalence values might be due to the ethnicity of the participants, as previous investigations revealed that anatomical structures, e.g., the angulation of the articular eminence, varies between different ethnical groups [4].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Temporomandibular joint (TMJ) sounds are categorized as cardinal symptoms of temporomandibular disorders (TMD) [1]. According to a systematic review, 14.0% of the children or adolescents had clinical TMJ sounds [2], while a current investigation detected an even higher percentage-up to 31.9%-for German adolescents [3]. The gap between prevalence values might be due to the ethnicity of the participants, as previous investigations revealed that anatomical structures, e.g., the angulation of the articular eminence, varies between different ethnical groups [4].…”
Section: Introductionmentioning
confidence: 86%
“…A cross-sectional sample of the LIFE Child Study, aged 10 to 18 years, was recruited to investigate physical parameters as well as characteristics of the masticatory and dental system of the participants, the procedure has already been described in detail elsewhere [3,14,15]. Temporomandibular joint sounds were examined by trained dentists who used the examination form of the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) [16].…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] Reported TMD prevalence in children and adolescents varies widely in the literature from 4.2% to 68%, depending on population and method of assessment. [5][6][7][8][9] Painful and dysfunctional TMD might be associated with emotional stress, depression, sleep and hormonal disturbances, and functional complications. [10][11][12] In turn, the patient's daily life will be adversely affected by the presence of a TMD; in addition, TMDs result in increased pursuit of medical care which consumes both time and money.…”
Section: Introductionmentioning
confidence: 99%
“…13 TMDs are a considerable health problem in children and adolescents; several studies consistently show that TMD prevalence increases with age from childhood to adolescence, 7-9,14,15 especially for females. 7,8 However, in children under the age of 10 prevalence is assessed mainly on self-reported or proxy-reported signs and symptoms; hence, there is a need to develop a more comprehensive standardised process for the collection of clinical information and the diagnosis of TMD in children and adolescents, so that reliability and validity can be assessed and improved for this population. 16 Since 2014, the international standard for the assessment of TMDs is the Diagnostic Criteria for TMD (DC/TMD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation